Ameliorating Device Efficiency of Perovskite Solar Cells via Low‐Cost Interfacial Modification between SnO2 and Perovskite Absorber - Ching‐Ying Wang; Sheng‐Hsiung Yang (Advanced Energy & Sustainability Research, 2025)
To reduce surface defects and tune mismatched energy levels between the tin oxide (SnO2) electron transport layer (ETL) and perovskite absorber, a mixture of urea and potassium acetate (U‐PA) is firstly utilized as a healing agent. The perovskite film deposited on the SnO2/U‐PA layer exhibits enlarged grains and shortened carrier lifetime compared to that on the pristine SnO2. The U‐PA treatment not only ameliorates the photocurrent but also adjusts interfacial energy level alignment, thereby reducing the energy barrier and augmenting open‐circuit voltage (VOC) of the photovoltaic devices. The device based on the SnO2/U‐PA ETL leads to the best conversion efficiency breakthrough of 19.24% and a high VOC of 1084.5 mV, which are much higher than those of the controlled device. Moreover, the unencapsulated device retains 70% of its initial efficiency after 800 h storage. The experimental results provide a facile and inexpensive guidance toward sustainable green energy production.